2015
DOI: 10.1093/mutage/gev007
|View full text |Cite
|
Sign up to set email alerts
|

Wood dust exposure induces cell transformation through EGFR-mediated OGG1 inhibition

Abstract: A high risk of neoplastic transformation of nasal and paranasal sinuses mucosa is related to the occupational exposure to wood dust. However, the role of occupational exposures in the aetiology of the airway cancers remains largely unknown. Here, an in vitro model was performed to investigate the carcinogenic effect of wood dusts. Human bronchial epithelial cells were incubated with hard and soft wood dusts and the DNA damage and response to DNA damage evaluated. Wood dust exposure induced accumulation of oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…17 OGG1 has also been shown to affect the cell transformation in wood dust exposure-induced or asbestos-induced pulmonary fibrosis in mice. 18,19 Whole transcriptome analysis showed that OGG1 plays an important role in tissue remodeling, and affects the actin cytoskeleton, the ECM, cell adhesion, cadherin, and cell junctions. 20 In this study, we focused on the mechanisms by which OGG1 affects TGF-β1-driven repair using both in vitro and in vivo approaches.…”
Section: Introductionmentioning
confidence: 99%
“…17 OGG1 has also been shown to affect the cell transformation in wood dust exposure-induced or asbestos-induced pulmonary fibrosis in mice. 18,19 Whole transcriptome analysis showed that OGG1 plays an important role in tissue remodeling, and affects the actin cytoskeleton, the ECM, cell adhesion, cadherin, and cell junctions. 20 In this study, we focused on the mechanisms by which OGG1 affects TGF-β1-driven repair using both in vitro and in vivo approaches.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that activation of EGFR/AKT/mTOR pathway induced the phosphorylation and subsequent inactivation of tuberin thus resulting in inhibition of OGG1 expression, consistent with results obtained by Habib. Therefore, the reduced expression of OGG1 determined DNA lesion accumulation, cell survival and proliferation ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a link between EGFR signaling and DNA repair mechanisms has been shown previously ( 47 , 48 ). Staffolani and colleagues demonstrated that in a human lung cell line, EGFR down-regulates wood-dust-induced OGG1 expression via AKT ( 49 ). However, to date, correlation between the BER and ErbB systems in gastric cancer has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…After 24 h or 48 h of treatment, 10 µL of MTT (5 mg/mL in PBS) was added to each well and the plate was incubated again for 3 h at 37 °C in incubator. Next, medium was removed, 200 µL of isopropanol was added, and the absorbance was read at 595 nm [ 73 ]. Cell viability rate was calculated following the formula: cell viability (%) = (average OD value of AITC-treated cells/average OD value of control cells) × 100.…”
Section: Methodsmentioning
confidence: 99%